Nanogenerator-Based Sensors for Energy Harvesting From Cardiac Contraction - Al-Suhaimi, Ebtesam Abdullah; Aljafary, Meneerah Abdulrahman; Alfareed, Tahani M.; Alshuyeh, Hussah Abdullah; Alhamid, Galyah Mohammed; Sonbol, Bayan; Almofleh, Atheel; Alkulaifi, Fadwa Mohammed; Altwayan, Reham Khalid; Alharbi, Jamilah Naif; Binmahfooz, Noha Mubarak; Alhasani, Eman Saleh; et al. (Frontiers in Energy Research, 2022)
Biomedical electric devices provide great assistance for health and life’s quality. However, their maintainable need stays a serious issue for the restricted duration of energy storage. Therefore, scientists are investigating alternative technologies such as nanogenerators that could harvest the mechanical energy of the human heart to act as the main source of energy for the pacemaker. Cardiac contraction is not a source for circulation but utilizing body energy as an alternative energy source to recharge pacemaker devices. This is a key biomedical innovation to protect patient’s lives from possible risks resulting from repeated surgery. A batteryless pacemaker is possible via an implantable energy collecting tool, exchanging the restriction of the current batteries to a sustainable self-energy resource technique. In this context, the physiology of heart energy in the preservation of blood distribution pulse generation and the effects of cardiac hormones on the heart’s pacemaker shall be outlined. In this review, we summarized different technologies for the implantable energy harvesters and self-powered implantable medical devices with emphasis on nanogenerator-based sensors for energy harvesting from cardiac contraction. It could conclude that recent hybrid bio-nanogenerator systems of both piezoelectric and triboelectric devices based on biocompatible biomaterials and clean energy are promising biomedical devises for harvesting energy from cardiac and body movement. These implantable and wearable nanogenerators become self-powered biomedical tool with high efficacy and durability, thin, flexible, and low cost. Although many studies have proven its safety, but there is a need for its long-term biosafety and biocompatibility. A further note on biocompatibility of bio-generator sensors shall be addressed.